2015
DOI: 10.1103/physrevlett.114.237402
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic Metamaterials with Bragg Polaritons

Abstract: We propose a novel mechanism for designing quantum hyperbolic metamaterials with the use of semiconductor Bragg mirrors containing periodically arranged quantum wells. The hyperbolic dispersion of exciton-polariton modes is realized near the top of the first allowed photonic miniband in such a structure which leads to the formation of exciton-polariton X waves. Exciton-light coupling provides a resonant nonlinearity which leads to nontrivial topologic solutions. We predict the formation of low amplitude spatia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…2.55 [5]. The second photonic band is convex that provides anomalous dispersion even in the center of the 1st BZ.…”
Section: Bragg Polaritons With Convex Dispersionmentioning
confidence: 89%
See 3 more Smart Citations
“…2.55 [5]. The second photonic band is convex that provides anomalous dispersion even in the center of the 1st BZ.…”
Section: Bragg Polaritons With Convex Dispersionmentioning
confidence: 89%
“…Recently it has been shown that the modified Bragg mirror structures can act as hyperbolic dispersion materials for Bragg polaritons [5][6][7]. The effects of reduction of the group velocity and the strong negative refraction have been predicted in them.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, they can form localized nondiffracting X-waves [15,16] which could be used for transferring a classical signal between elements in the circuits. Thus, polaritonics is regarded as a future of new photonic-electronic devices, which will be capable of processing information at a rate of terabits per second and frequencies in the range 100 GHz-10 THz [17].…”
Section: Introductionmentioning
confidence: 99%